Alterations in the Cell Wall of Rhodococcus biphenylivorans Under Norfloxacin Stress - Jia, Yangyang; Yu, Chungui; Fan, Jiahui; Fu, Yulong; Ye, Zhe; Guo, Xiaoguang; Xu, Ying; Shen, Chaofeng (Frontiers in Microbiology, 2020)
Many microorganisms can enter a viable but non-culturable (VBNC) state under various environmental stresses, while they can also resuscitate when the surroundings turn to suitable conditions. Cell walls play a vital role in maintaining cellular integrity and protecting cells from ambient threats. Here, we investigated the alterations in the cell wall of Rhodococcus biphenylivorans TG9 at VBNC state under norfloxacin stress and then at resuscitated state in fresh lysogeny broth medium. Electron microscopy analyses presented that TG9 in the VBNC state had a thicker and rougher cell wall than that in exponential phase or resuscitated state. Meanwhile, the results from infrared spectroscopy also showed that its VBNC state has different peptidoglycan structures in the cell wall. Moreover, in the VBNC cells the gene expressions related to cell wall synthesis and remodeling maintain a relatively high level. It indicates that the morphological variations of TG9 at the VBNC state might result from kinetic changes in the cell wall synthesis and remodeling. As a consequence, the alterations in the cell wall of VBNC TG9 may somewhat account for its tolerance mechanisms to antibiotic treatment.